Literary Citizenship in Scandinavia in the Long Eighteenth Century - Hemstad, Ruth (Knowledge and Communication in the Enlightenment World Series., 2023)
Sheds new light on European and regional book markets, the development of a public sphere and the impact of new media on intellectual, social, religious and political change.